Efforts to Invest in Human Resources through Competence in order to Improve the Performance of Social Assistants of the Family Hope Program in Nias Regency - Denniska Halawa; Fentiny Nugroho (Cita Konsultindo Research Center, 2024)
PKH (Program Keluarga Harapan/Family Hope Program) is one of the poverty reduction intervention efforts to realize social welfare for the community. The process of implementing the program requires Human Resources as the driving force of the program itself. Therefore, it is necessary to ensure the quality of human resources as PKH Social Assistants are one of the resources of social welfare providers employed by the Government to ensure PKH is implemented according to the provisions. This study aims to determine the efforts made in investing in human resources through strengthening competencies to PKH social assistants and identifying the impact of strengthening these competencies on the performance of PKH social assistants in Nias Regency. The method used was qualitative by interviewing 11 informants. The focus aspects of this study's competencies refer to the three basic components that a person must have in developing the profession of practitioners in the field of social welfare, namely knowledge, skills and values. This study concludes that there is an impact received by Nias Regency Social Assistants, namely increased insight, increased technical ability, and increased commitment to work so that in the implementation of daily work or the performance of PKH social assistants can be more improved or of higher quality.